(untitled) (Iranian Journal of Kidney Diseases, 2022)
Introduction. We intended to explore the prevalence of chronic kidney disease (CKD) and its different stages, as well as CKD associated variables in the adult population in Isfahan province, Iran. Methods. Adults aged ≥ 18 were recruited in a cross-sectional study from 2017 to 2019. Data including demographics, anthropometrics, and laboratory findings were collected from each subject. The equation of chronic kidney disease- Epidemiology Collaboration (CKD-EPI) was used to estimate glomerular filtration rate (eGFR), and eGFR and UACR values were utilized to determine the stages of CKD. Results. Data from a total of 3374 subjects was analyzed. The mean age of participants was 49.3 ± 14.09 years and 59.3% were female. The prevalence of CKD was 18.5%. Only 0.25 and 3.5% of the population were in CKD stage 3 and 4, while most of the patients were in CKD stage 2 (7.6%) and stage 1 (7.1%). CKD patients were mostly on refined grains diet and used lesser dairy products compared to healthy participants. Variables including systolic blood pressure (OR = 1.018; P < .001), diastolic blood pressure (OR = 1.005; P < .05), fasting blood sugar (OR = 1.011; P < .001), female sex (OR = 1.319; P < .05), body mass index (OR = 1.030; P < .05), married status (OR = 1.335; P < .05), and smoking (OR = 1.529; P < .05) were significantly associated with increased risk of CKD in the logistic regression analysis. Conclusion. According to our results, the prevalence of CKD, especially stages 1 and 2, is quite high in central part of Iran. These findings help us to improve the screening for CKD patients and perform larger scale studies to identify the challenges ahead. DOI: 10.52547/ijkd.7201